"Marketing Monsters: a Reading of Christina Rossetti's Goblin Market&#34 - Jukić, Tatjana (Array, 2002)
The text explores the ways in which the fantastic of Christina Rossetti's Goblin Market evolves into the parable of its own interpretive consumption, in contemporary feminist and psychoanalytic criticism.